Alpha–gamma transition in RF capacitive discharge in low-pressure oxygen - Lisovskiy, V.; Yegorenkov, V. (www.elsevier.com/locate/vacuum, 2004)
We report the recorded current–voltage characteristics of a RF capacitive discharge in oxygen. Low-frequency oscillations of the plasma potential in a kilohertz frequency range are observed to accompany the transition of the discharge from a weak- (a-) to a strong-current (g-) regime in the low-pressure range. The weak-current regime of the RF capacitive discharge is observed within the pressure range limited not only from the medium pressure side but also from the lower-pressure one. Electron temperature and plasma density are registered with a probe technique.
Keywords: plasma physics; gas discharges